Saving Behaviour: Factors That Affect Saving Decisions (Systematic Literature Review Approach) - Bayu Bastian Jumena; Steven Siaila; Joko Rizkie Widokarti (Jurnal Economic Resource, 2022)
Savings have an important role as alternative funding when the primary income is in trouble. Previous research on saving behavior has been carried out fragmentary, which causes the conclusions to be partial. Therefore, it is necessary to research with a systematic literature review method to obtain a complete conclusion about the factors that can influence individual saving decisions. In this study, the articles used consisted of 124 published by Elsevier from 2012-2021. The results show that over the past ten years, research on saving behavior has been carried out in 185 countries and ten regions, with the method used consisting of 18 analytical methods. The results of the meta-synthesis show that 15 factors can influence the saving decision, viz: personal wealth, individual needs and dependency, macroeconomic, demographic, financial literacy, anticipatory, psychological and social, profit, self-obligation, financial service, savings product marketing, job profile, self-preference, financial goals, and geographic. The fifteen factors are classified into two groups: internal factors (consisting of 10 factors) and external factors (consisting of 5 factors).